The Effects of Online Games on the Students’ Motivation and Its Implications in Learning - Dwi Anita Alfiani; Fikri Miftahul Nugraha; Heru Mudiyanto; Dadan Setiawan (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThis study is inspired by the explosive growth the information technology industry that has affected every aspect of life, including the field of education. In this highly modern era, online games have developed rapidly and become favored by students. This study sought to ascertain how internet games affected the learning motivation of sixth-grade students at Madrasah Ibtidaiyah in Cirebon City, West Java, Indonesia. Employing experimental research methods, this study was ex post facto in design. The participants of this study were 21 sixth-grade elementary school students at Madrasah Ibtidaiyah in Cirebon City, West Java, Indonesia. In this study, a non-random sampling method was applied for the sampling process. Interviews and questionnaires were used to gather the research's data. Using both descriptive and inferential statistics, the research data were examined. According to the study's findings, 67% of students engaged in online gaming with a medium level of intensity. Meanwhile, the student's level of motivation for learning was low, at 67%. These findings suggest that playing online games does not increase the students' enthusiasm for learning, and may even have the opposite effect by contributing to the low student motivation.Keywords: game online, learning motivation, madrasah ibtidaiyah.AbstrakPenelitian ini dilatarbelakangi oleh ledakan pertumbuhan industri teknologi informasi yang telah mempengaruhi setiap aspek kehidupan, termasuk bidang pendidikan. Di era yang sangat modern ini, game online telah berkembang pesat dan disukai oleh kalangan pelajar. Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh internet games terhadap motivasi belajar siswa kelas VI di salah satu Madrasah Ibtidaiyah di Kota Cirebon, Jawa Barat, Indonesia. Dengan menggunakan metode penelitian eksperimen, penelitian ini berdesain ex post facto. Partisipan penelitian ini adalah 21 siswa kelas 6 (enam) di salah satu Madrasah Ibtidaiyah di Kota Cirebon, Jawa Barat, Indonesia. Dalam penelitian ini digunakan metode non random sampling untuk proses pengambilan sampel. Wawancara dan kuesioner digunakan untuk mengumpulkan data penelitian. Menggunakan kedua statistik deskriptif dan inferensial, data penelitian diperiksa. Menurut temuan penelitian, 67% siswa terlibat dalam game online dengan intensitas sedang. Sedangkan tingkat motivasi belajar siswa rendah yaitu 67%. Temuan ini menunjukkan bahwa bermain game online tidak meningkatkan semangat siswa untuk belajar, dan bahkan mungkin memiliki efek sebaliknya dengan memberikan kontribusi terhadap rendahnya motivasi belajar siswa.Kata kunci: game online, motivasi belajar, madrasah ibtidaiyah.